Colours of the Alphabet - Cole, Alastair (United Kingdom ; New Zealand : Lansdowne Productions ; Tongue Tied Films, 2016)
Alastair Cole’s feature debut 'Colours of the Alphabet' is a beautiful, inspiring and bittersweet documentary film about language and childhood in Africa. Steward, Elizabeth and M'barak are three young pupils starting school in rural Zambia who struggle to make sense of an educational system where the language they speak at home is different from the language used in the classroom. Moments of perplexed incomprehension, both comedic and tragic ensue, as the children slowly come to terms with the fact that their tongue is no longer their own. At a time when nearly 40% of the world's population lack access to education in their own language, 'Colours of the Alphabet' offers an intimate and moving insight into a global phenomenon from the unique perspective of three innocent children.
Verzio Film Festival Submission
Keywords: Documentary films